Advances in nanoengineering: electronics, materials, assembly. - Davies, A. G; Davies, A. G; Thompson, J. M. T (Royal Society series on advances in science, 2007)
This book outlines a selection of exciting advances currently being made worldwide in the field of modern engineering at the nanometer scale. Leading scientists and engineers give a general overview of research advances in their specialized subject areas. They also describe some of their own cutting-edge research and give their visions of the future. Written in a popular and well-illustrated style, the articles are written by young scientists many of whom hold, or have held, prestigious Royal Society or EPSRC Fellowships. Carefully selected by Professor A G Davies and Professor J M T Thompson FRS, topics include: the fabrication and measurement of nanoelectronic devices, organic conductors, and bioelectronic materials; the assembly of such structures into appropriate configurations, including the use of biological processes to drive the assembly; the development of new materials including both organic and inorganic wires, carbon nanotubes, and magnetic materials; and finally, the analysis and characterization of these structures.